Chikungunya masquerading as dengue infection in Sri Lanka uncovered by metagenomics - K. M. Ahsanul Kabir; Chathurani Sigera; Sachith Maduranga; Praveen Weeratunga; Senaka Rajapakse; Deepika Fernando; Andrew R. Lloyd; Rowena A. Bull; Chaturaka Rodrigo (PLoS ONE, 2025)
Introduction Dengue is a significant threat to human health in South and Southeast Asia where patients are treated without diagnostic confirmation during outbreaks. This approach, though cost-effective may miss important infections especially those caused by other arboviruses (e.g., Zika, Chikungunya and West Nile virus). This study aimed to diagnose missed infections mimicking dengue by using metagenomic next generation sequencing (mNGS). Methods and principal findings Total nucleic acid (DNA and RNA) was extracted and subjected to mNGS from acute infection plasma of 60 patients from a prospective cohort study in Sri Lanka in which patients with clinically suspected dengue fever were recruited but were later confirmed as dengue-negative by NS1 antigen testing and by dengue-specific reverse transcription and polymerase chain reaction (RT-PCR) analysis. mNGS data revealed missed chikungunya and dengue infections in five patients each, and a possible bacterial infection by Klebsiella pneumoniae in another patient. It was not possible to differentiate chikungunya infections from dengue infections based on clinical features or routine non-diagnostic laboratory tests conducted in early infection (e.g., full blood count, C-reactive protein level). Phylogenetic analysis showed that the chikungunya sequences from this study were closely related to those sequenced from Maldives, Malaysia, India and Singapore between 2015–2019. Conclusions Chikungunya infection may masquerade as dengue especially in low- and middle-income countries where dengue is treated based on clinical suspicion only – without confirmatory testing. As both infections are likely prevalent worldwide, but the complications and natural history of chikungunya and dengue infections are quite different, the addition of cheap and accessible diagnostics for both infections should be pursued in endemic countries.